The Role of Long Non-coding RNAs in Immunotherapy Resistance - Zhou, Yuwen; Zhu, Yajuan; Xie, Yao; Ma, Xuelei (Frontiers in Oncology, 2019)
T-cell-based immunotherapies, particularly immune checkpoint inhibitors, are promising treatments for various cancers. However, a large subset of patients develop primary or secondary resistance upon treatment. Although the detailed mechanisms remain unclear, immune escape via alterations in both cancer and tumor microenvironment has been identified as critical causes of immune resistance. Moreover, some long non-coding RNAs (lncRNAs), named as immune-related lncRNAs, have been recognized as regulators of immune cell-specific gene expression that mediate immune processes. These immune-related lncRNAs may play a vital role in immunotherapy resistance. Herein, we summarize current immune-related lncRNAs and their underlying roles in immune resistance to provide strategies for future research and therapeutic alternatives to overcome immunotherapy resistance.